1980
DOI: 10.1083/jcb.87.3.546
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the turning response of dorsal root neurites toward nerve growth factor.

Abstract: This study reports that chick dorsal root ganglion neurites undergo a rapid (20 min) reorientation of their direction of growth in response to nerve growth factor (NGF) concentration gradients in vitro. Dorsal root ganglia from chick embryos were explanted onto a collagen-poly-L-lysine substrate. After 24-48 h in culture, NGF gradients were applied to individual growth cones via a micropipette containing 50 biological units NGF/ml. The growth cones turned and grew toward these NGF sources. This turning respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
185
1
2

Year Published

1993
1993
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 471 publications
(197 citation statements)
references
References 24 publications
9
185
1
2
Order By: Relevance
“…S5, available at www.jneurosci.org as supplemental material) (Nagata-Ohashi et al, 2004). We confirmed that application of an NGF gradient results in an attractive mean turning angle when applied to E8 chick DRG growth cones (Gundersen and Barrett, 1980;Gehler et al, 2004) and we find that this response is unaffected by HSV-R18-GFP (12.6 Ϯ 5.8°; Fig. 2a,d).…”
Section: -3-3 Proteins Are Expressed In Neuronal Growth Conessupporting
confidence: 79%
“…S5, available at www.jneurosci.org as supplemental material) (Nagata-Ohashi et al, 2004). We confirmed that application of an NGF gradient results in an attractive mean turning angle when applied to E8 chick DRG growth cones (Gundersen and Barrett, 1980;Gehler et al, 2004) and we find that this response is unaffected by HSV-R18-GFP (12.6 Ϯ 5.8°; Fig. 2a,d).…”
Section: -3-3 Proteins Are Expressed In Neuronal Growth Conessupporting
confidence: 79%
“…While previous studies demonstrated neurite outgrowth towards a neurotrophic factor source, the concentration pro®le was ill-de®ned. For example, neurite outgrowth towards a point source was studied, with the source created either by micropipetting factors at a speci®c location in culture media 18,19,38 or using explants which released the factors of interest. 28 In both examples, the concentration pro®le was either poorly de®ned 29 or Gaussian, 22 and depended upon the experimental geometry and other parameters used.…”
Section: Discussionmentioning
confidence: 99%
“…This may explain the discrepancy in the literature between cellular response to different concentrations and concentration gradients. 18,28 To create a linear, stable, homogeneous concentration gradient throughout the agarose gel, a constant concentration of NGF was provided in both source and sink compartments while the steady-state diffusion was established. To achieve constant concentrations of NGF in both source and sink compartments, the NGF solutions in both compartments were replenished every 6 h during the course of the experiment; this ensured a concentration difference¯uctuation of less than 1% between each solution replenishment, according to our calculation (cf.…”
Section: Discussionmentioning
confidence: 99%
“…NGF has been shown to prevent the complete death of axotomized sensory neurons following exogenous administration [58]. There is enough evidence to show that gradients of neurotrophins help in guiding developing as well as regenerating axons in a wide variety of neuronal systems [59,60]. Although many in vitro studies have shown influence of gradients of LN-1 and NGF for neurite extension, to our knowledge, there are no in vivo studies with gradients, due to the difficulties in making and sustaining gradients in vivo.…”
Section: Discussionmentioning
confidence: 99%